The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10792-017-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness in chronic rhegmatogenous retinal detachment before and after surgery, and comparison with acute cases

Abstract: No significant difference was found in the mean SCT between affected and fellow eyes in chronic RRD. This may be related to intraocular inflammation, which is more limited in chronic than in acute RRD. There was also no significant difference in the SCT in eyes with chronic RRD between the operated and fellow eyes after surgery. It may be concluded that vitrectomy does not affect choroidal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Changes in the choroidal thickness have been reported in various eye diseases [19][20][21]. Kimura et al reported that the mean choroidal thickness increased in eyes with RRD compared to fellow eyes preoperatively [22].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the choroidal thickness have been reported in various eye diseases [19][20][21]. Kimura et al reported that the mean choroidal thickness increased in eyes with RRD compared to fellow eyes preoperatively [22].…”
Section: Discussionmentioning
confidence: 99%
“…Flow of fluid from the posterior chamber, into the subretinal space reaching the retinal pigment epithelium, is believed to be a consequence of RD and can cause choroidal thickening. 15 CT has also been shown to decrease with age, a possible 16 Therefore, we believe that age is not a primary contributor to the significant CT increase observed in Group 2 patients. Successful RD surgery is normally associated with incomplete visual acuity recovery; however, some improvement is normally observed.…”
Section: Discussionmentioning
confidence: 79%
“…Later, owing to the removal of the vitreous body and ERM, the oxygen and nutrient supply to the retinal tissues improve, and the thickness of the choroid is expected to decrease. Taking into account studies that showed no change in choroidal thickness before and after vitrectomy in patients with macular hole [ 11 , 12 , 16 ] and patients with rhegmatogenous retinal detachment [ 17 , 18 ], the effect of internal limiting membrane peeling and vitreous removal on choroidal thickness is not considered significant. Therefore, the decrease in choroidal thickness after surgery in this study was considered an effect of ERM removal.…”
Section: Discussionmentioning
confidence: 99%